Postoperative Long-Term Independence Among the Elderly With Meningiomas: Function Evolution, Determinant Identification, and Prediction Model Development - Li, Haoyi; Huang, Huawei; Zhang, Xiaokang; Wang, Yonggang; Ren, Xiaohui; Cui, Yong; Sui, Dali; Lin, Song; Jiang, Zhongli; Zhang, Guobin (Frontiers in Oncology, 2021)
Background Maintenance of postoperative long-term independence has value for older adults who undergo surgical procedures. However, independence has barely caught attention for the elderly with meningiomas. Preventing postoperative long-term independence decline in this population necessitates the identification of the factors related to this outcome and minimizing their implications. Therefore, we assessed the independence evolution and identified potential determinants and population. Materials and Methods From 2010 to 2016, elderly meningioma patients (≥65 years old) undergoing operation at Beijing Tiantan Hospital were included in our study. The primary outcome was 3-year (i.e., long-term) postoperative independence measured by Karnofsky performance scale (KPS) score. We used univariate and multivariate analyses to determine the risk factors for postoperative long-term independence, and nomogram was established. Results A total of 470 patients were included eligibly. The distribution in each KPS was significantly different before and 3 years after resection (P < 0.001). Especially in patients with preoperative KPS 80 and 70, only 17.5 and 17.3% of the patients kept the same KPS after 3 years, and the remaining patients experienced significant polarization. The most common remaining symptom cluster correlated with postoperative long-term independence included fatigue (R = −0.795), memory impairment (R = −0.512), motor dysfunction (R = −0.636) and communication deficits (R = −0.501). Independent risk factors for postoperative long-term non-independence included: advanced age (70–74 vs. 65–69 OR: 2.631; 95% CI: 1.545–4.481 and ≥75 vs. 65–69 OR: 3.833; 95% CI: 1.667–8.812), recurrent meningioma (OR: 7.791; 95% CI: 3.202–18.954), location in the skull base (OR: 2.683; 95% CI: 1.383–5.205), tumor maximal diameter >6 cm (OR: 3.089; 95% CI: 1.471–6.488), nerves involved (OR: 3.144; 95% CI: 1.585–6.235), high risk of WHO grade and biological behavior (OR: 2.294; 95% CI: 1.193–4.408), recurrence during follow-up (OR: 10.296; 95% CI: 3.253–32.585), lower preoperative KPS (OR: 0.964; 95% CI: 0.938–0.991) and decreased KPS on discharge (OR: 0.967; 95% CI: 0.951–0.984) (P < 0.05). The discrimination and calibration of the nomogram revealed good predictive ability (C-index: 0.810). Conclusion Elderly meningioma patients might present significant polarization trend in maintaining long-term independence after surgery. Our findings will be helpful for guiding surgical management for the elderly with meningioma and provide proposals for early functional rehabilitation.